Formulasi dan penentuan Nilai SPF Ekstrak Etanol Daun Kemangi (Ocimum sanctum L.) Sediaan Krim Tabir Surya - Fahmi Nur Endahsari; Susi Endrawati; Sri Saptuti Wahyuningsih (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2022)
Basil leaves are a common plant for the community. Usually basil leaves (Ocimum sanctum L.) are used as fresh vegetables. Basil leaves contain flavonoids and tannins which have potential as sunscreen. This study aims to determine the value of SPF and formulation cream of ethanol extract of basil leaves as sunscreen and his research is an experimental study by testing the SPF value of the ethanol extract of basil leave as sunscreen by extracting the basil leaves with the remaceration method using 96% ethanol and tested using the UV-Vis spectrophotometric method. The test preparation includes organoleptic test, pH measurement, homogeneity test, spreadability test, adhesion test, protective power test. The result of the evaluation of the preparatios were calculated on average andanalyzed by the ANOVA test. The result determining the SPF value of the ethanol extract of basil leaves at a concentration of 800 pm,1000 ppm,1200 ppm, 1400 ppm, and 1600 ppm obtained SPF values respectively : 17,73 ± 0,90; 21,17 ± 0,06; 25,59 ± 0, 35; 30,54 ± 0,22; 62,56 ± 0,14. The ethanol extract of basil leaves (Ocimum sanctum L.) with an extract concentration of 1600 ppm was 62,56 ± 0,14 based on the Food and Drug Administrastion (FDA) the SPF value is in the high protection category because it has an SPF value above 30. The ethanol extact of basil leaves has the potential as a sunscreen.